A copolymer for lithium ion battery cathode binder and a preparation method thereof
Patent Information
- Application Number
- CN202311573504.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-23
AI Technical Summary
但用于高镍的三元材料时,材料的碱性强,还是容易发生凝胶现象
[0024]1、本发明所述共聚物,与PVDF相比,具有高粘结力,采用两亲性单体而非亲水性单体制备得到的共聚物在提高共聚物在溶剂中的分散性的同时,吸水率更低,不易发生凝胶现象,能够提升锂电池的高相容性、耐高低温、以及稳定的充放电效率;尤其是所述共聚物中引入氯乙烯及其衍生单元,使共聚物在用于粘结剂时表现出良好的阻燃性和耐酸碱性,能够很好的替代PVDF。
Smart Images

Figure BDA0004566224190000081 
Figure BDA0004566224190000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically to a copolymer for use as a binder in the positive electrode of lithium-ion batteries and its preparation method. Background Technology
[0002] Nickel-rich layered metal oxides (also known as ternary materials, LiNi) 1-x-y Co x Mn y O2 is considered an ideal cathode material for lithium batteries, but Ni 3+ Irreversible redox reactions between the battery and the electrolyte can lead to a decrease in battery capacity and durability.
[0003] To address the aforementioned issues, a mixed solution of commercially available polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) is widely used for bonding ternary electrode materials. PVDF, in particular, possesses a high dielectric constant, good chemical stability and temperature characteristics, and exhibits excellent mechanical properties and processability. However, it also has some drawbacks, such as: a high Young's modulus leading to poor flexibility in the resulting electrode sheets; deterioration in bonding performance at high temperatures; and significant swelling under electrolyte immersion, which is detrimental to battery safety. Furthermore, due to the high technical difficulty of production, the total domestic production capacity of PVDF suitable for practical application in lithium-ion battery binders is low, and its price is high.
[0004] Furthermore, due to the high nickel content and strong alkalinity of ternary materials, PVDF will lose HF molecules in this strongly alkaline environment, forming double bonds on the main chain. These double bonds readily react with oxygen in the air to generate peroxides. The decomposition of peroxides produces oxygen free radicals, which ultimately lead to gelation of the slurry due to self-coupling. Current technologies address this issue by introducing special polyfluorinated monomers during PVDF polymerization, such as trifluorochloroethylene, hexafluoropropylene, hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, dodecafluoroheptyl methacrylate, and carboxyl-containing vinyl monomers, to reduce the head-and-tail structure of hydrogen and fluorine linkages. However, when used in high-nickel ternary materials, the strong alkalinity of the material still makes gelation easy. If traditional water-based binders such as carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and polyvinyl alcohol (PVA) are used, the residual moisture in these binders will damage the structure of the ternary material. Summary of the Invention
[0005] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide a copolymer for lithium-ion battery cathode binders and its preparation method. This copolymer is characterized by its resistance to gelation and high adhesion, and can replace the traditional cathode binder PVDF. Furthermore, it can be prepared using a simple and low-cost method, thereby solving the problems of existing binders being prone to gelation and exhibiting poor adhesion performance at high temperatures.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] A copolymer for use as a binder in the positive electrode of a lithium-ion battery, wherein the comonomers of the copolymer include lipophilic monomers, amphiphilic monomers, and vinyl chloride derivatives; based on the total mass of the lipophilic monomers, the amphiphilic monomers, and the vinyl chloride derivatives: the mass percentage of the amphiphilic monomers is 10-20%, the mass percentage of the lipophilic monomers is 60-80%, and the mass percentage of the vinyl chloride derivatives is 10-30%.
[0008] The amphiphilic monomer in this invention possesses both hydrophilic and lipophilic functional groups, which helps the polymer to be more uniformly dispersed in the solvent and reduces gelation. The vinyl chloride derivative has a lower glass transition temperature, giving the copolymer better processability when used as a binder in lithium-ion batteries, resulting in electrodes with better flexibility. Furthermore, the chlorine-containing copolymer exhibits better flame retardancy, enhancing battery safety at high temperatures.
[0009] Preferably, the vinyl chloride derivative is a vinyl chloride derivative obtained by mono- or multi-substituted vinyl chloride; wherein the vinyl chloride derivative is liquid or solid at room temperature and pressure.
[0010] More preferably, the vinyl chloride derivative is 1,2-dichloroethylene.
[0011] Preferably, the lipophilic monomer includes acrylonitrile and / or methacrylonitrile.
[0012] Preferably, the amphiphilic monomer includes one or more combinations of dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate.
[0013] More preferably, the amphiphilic monomer is dimethylaminoethyl methacrylate.
[0014] The present invention also provides a method for preparing a copolymer for use as a binder in the positive electrode of a lithium-ion battery. The preparation of the copolymer specifically includes the following steps:
[0015] Step 1: Mix the amphiphilic monomer, lipophilic monomer, and vinyl chloride derivative according to the specified ratio, and then prepare a mixture of the reactant monomer and water. Then, add the emulsifier and water to the reactor for deoxygenation, stir evenly, and slowly add the mixture of monomer and water while stirring continuously to form a pre-emulsion. The amount of emulsifier used is 3-6% of the total weight of the reactant monomer.
[0016] Step 2: Divide the pre-emulsion obtained in Step 1 into two parts. Add one part of the pre-emulsion to the reactor for deoxygenation, heat it to 67-72°C, add an initiator to react, and obtain a seed emulsion. Then slowly add the other part of the pre-emulsion. After the reaction is completed, cool it down, demulsify it, filter and dry it to obtain the copolymer. The amount of initiator used is 0.05-0.8% of the total weight of the reacting monomers.
[0017] Preferably, the emulsifier includes anionic emulsifier and nonionic emulsifier, wherein the amount of anionic emulsifier is 1 to 2% of the total weight of the reactant monomers, and the amount of nonionic emulsifier is 2 to 4% of the total weight of the reactant monomers.
[0018] Preferably, the anionic emulsifier is selected from one or a combination of at least two of sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium oleate; the nonionic emulsifier is selected from one or a combination of at least two of alkylphenol polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.
[0019] Preferably, the initiator comprises one or a combination of at least two of the following: ammonium persulfate, sodium persulfate, potassium persulfate, azobisisobutyrazoline hydrochloride, azobisisobutyramidine hydrochloride, azobiscyanopentanoic acid, azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovalerate, benzoyl peroxide, dodecyl peroxide, cumene hydroperoxide, diisopropyl peroxide, and dicyclohexyl peroxide.
[0020] Preferably, in step 2, the demulsifier used for demulsification includes one or a combination of at least two of sodium, magnesium, calcium chloride, carbonate, and sulfate salts.
[0021] The present invention also provides a positive electrode sheet for lithium-ion batteries, the positive electrode sheet comprising a positive electrode material, a conductive agent and a binder; the binder is formulated from the above-mentioned copolymer.
[0022] Preferably, the amount of binder used accounts for 1 to 3 wt% of the total solid content of the positive electrode slurry.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The copolymer described in this invention has high adhesive strength compared to PVDF. The copolymer prepared using amphiphilic monomers instead of hydrophilic monomers improves the dispersibility of the copolymer in solvents, while having a lower water absorption rate and being less prone to gelation. This can improve the high compatibility, high and low temperature resistance, and stable charge and discharge efficiency of lithium batteries. In particular, the introduction of vinyl chloride and its derivative units into the copolymer gives it good flame retardancy and acid and alkali resistance when used as a binder, making it a good substitute for PVDF.
[0025] 2. The preparation method of the copolymer described in this invention is simple and easy to operate, and the reaction conditions are not harsh. It can achieve industrial mass production in a low-cost manner and has good application prospects. Detailed Implementation
[0026] The present invention will be further described below with reference to embodiments.
[0027] Those skilled in the art will know that in the process of polymer polymerization, both "monomer" and "unit" refer to compounds that participate in the polymerization reaction; in this invention, "monomer" and "unit" have the same meaning.
[0028] In this invention, the term "A and / or B" means that A and B exist simultaneously, or only A exists, or only B exists.
[0029] I. A copolymer for use as a binder in lithium-ion battery cathodes
[0030] The copolymer's comonomers include amphiphilic monomers, lipophilic monomers, and vinyl chloride derivatives; based on the total mass of the lipophilic monomers, the amphiphilic monomers, and the vinyl chloride derivatives: the mass percentage of the amphiphilic monomers is 10-20%, the mass percentage of the lipophilic monomers is 60-80%, and the mass percentage of the vinyl chloride derivatives is 10-30%.
[0031] In some embodiments, the lipophilic monomer is an olefin derivative containing one or more lipophilic units selected from nitrile, ester, benzene ring, acyl chloride, glycerol ester, alkyl ester, and silane. In some preferred embodiments, the lipophilic monomer is acrylonitrile and / or methacrylonitrile. Acrylonitrile or methacrylonitrile has a strongly polar cyano group, which can form strong hydrogen bonds with the current collector and the positive electrode active material, providing high adhesion.
[0032] The vinyl chloride derivative is a vinyl chloride compound resulting from mono- or poly-substituted vinyl chloride; wherein the vinyl chloride derivative is liquid or solid at room temperature and pressure. The vinyl chloride derivative includes one or more combinations of 1,1-dichloroethylene, 1,2-dichloroethylene, 1,1,2-trichloroethylene, 1,1,2,2-tetrachloroethylene, 1-chloropropene, 2-chloropropene, 3-chloropropene, 1-chloro-2-methyl-1-propene, and 3-chloro-2-methylpropene. The vinyl chloride derivative is preferably 1,2-dichloroethylene.
[0033] While acrylonitrile and / or methacrylonitrile can provide strong adhesion, polymers prepared solely from acrylonitrile and / or methacrylonitrile are hard and brittle. When used as binders in lithium-ion batteries, the resulting electrodes lack flexibility and are prone to cracking during winding. Introducing vinyl chloride derivatives, whose C-Cl bonds also exhibit some polarity, provides a degree of adhesion. Furthermore, because C-Cl bonds are more easily rotated, the resulting copolymers possess better flexibility, compensating for the shortcomings of acrylonitrile / methacrylonitrile monopolymers.
[0034] In the embodiments of this invention, the amphiphilic monomer refers to an olefin derivative that simultaneously includes hydrophilic and lipophilic functional groups, such as simultaneously including hydroxyl and ester groups, or simultaneously including amino and ester groups, or simultaneously including carboxyl and ester groups, etc. In some preferred embodiments, the amphiphilic monomer may be one or more of dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate.
[0035] Amphiphilic monomers can improve the dispersibility of copolymers in solvents and reduce gelation. Preferred amphiphilic monomers contain ester groups, which can further provide flexibility to the copolymer.
[0036] II. A method for preparing a copolymer for use as a binder in lithium-ion battery cathodes
[0037] The preparation of the above copolymer specifically includes the following steps:
[0038] Step 1: Mix the amphiphilic monomer, lipophilic monomer, and vinyl chloride derivative according to the specified ratio to form a reactive monomer, and then prepare a mixture of reactive monomer and water; then add emulsifier and water to the reactor for deoxygenation, stir evenly, and slowly add the mixture of reactive monomer and water, and continue stirring to form a pre-emulsion; wherein, the amount of emulsifier is 3 to 6% of the total weight of the reactive monomer;
[0039] Step 2: Divide the pre-emulsion obtained in Step 1 into two parts. Add one part of the pre-emulsion to the reactor for deoxygenation, heat it to 70°C, add an initiator to react, and obtain a seed emulsion. Then slowly add the other part of the pre-emulsion. After the reaction is completed, cool it down, demulsify it, filter and dry it to obtain the copolymer. The amount of initiator is 0.05 to 0.8% of the monomer weight.
[0040] In some embodiments, the emulsifier includes anionic emulsifiers and nonionic emulsifiers, wherein the amount of anionic emulsifier is 1 to 2% of the monomer weight, and the amount of nonionic emulsifier is 2 to 4% of the monomer weight.
[0041] In some embodiments, the anionic emulsifier is selected from one or a combination of at least two of sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium oleate. Sodium dodecyl sulfonate is more preferred. The nonionic emulsifier is selected from one or a combination of at least two of alkylphenol polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester. Alkylphenol polyoxyethylene ether is more preferred.
[0042] In some embodiments, the initiator includes one or a combination of at least two of the following: ammonium persulfate, sodium persulfate, potassium persulfate, azobisisobutyrazoline hydrochloride, azobisisobutyramidine hydrochloride, azobiscyanopentanoic acid, azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovalerate, benzoyl peroxide, dodecyl peroxide, cumene hydroperoxide, diisopropyl peroxide, and dicyclohexyl peroxide.
[0043] In some embodiments, the demulsifier used in step 2 for demulsification includes one or a combination of at least two of sodium, magnesium, calcium chloride, carbonate, and sulfate salts.
[0044] In some embodiments, in step 2, the reaction is carried out for 5 to 7 hours after the initiator is added; and for 3 to 5 hours after the pre-emulsion is added.
[0045] III. A positive electrode sheet for lithium-ion batteries
[0046] The positive electrode sheet of the present invention comprises a positive electrode material, a conductive agent, and a binder; the binder is formulated from the above-mentioned copolymer.
[0047] In specific implementation, the binder is used in an amount accounting for 1-3 wt% of the total solids content of the positive electrode slurry. The binder is obtained by adding the copolymer to N-methylpyrrolidone and adjusting its solids content. Specifically, the copolymer is added to N-methylpyrrolidone (NMP) solvent and its solids content is adjusted to 7±1% to obtain the binder, which is used in an amount accounting for 1-3 wt% of the total solids content of the positive electrode slurry.
[0048] IV. Examples and Comparative Examples
[0049] Example 1
[0050] Step 1: According to the weight proportions, 80 parts of acrylonitrile, 10 parts of dimethylaminoethyl methacrylate, and 10 parts of 1,2-dichloroethylene are uniformly mixed in 250 parts of deionized water to prepare a monomer mixture. 2 parts of sodium dodecyl sulfonate, 3 parts of alkylphenol polyoxyethylene ether, and 150 parts of deionized water are added to a reaction vessel. Nitrogen gas is purged into the reaction vessel for 30 minutes to remove oxygen. Then, the mixture is stirred at 200 rpm / min for 1 hour. During stirring, the monomer mixture is slowly added, and stirring continues to form a stable pre-emulsion.
[0051] Step 2: Add 100 parts of the above pre-emulsion to a reactor equipped with a stirrer, thermometer, and condenser. Purge with high-purity nitrogen for 30 minutes to remove oxygen. After heating to 70°C, add 0.15 parts of ammonium persulfate to the pre-emulsion. After reacting for a period of time, a seed emulsion is obtained. Then, continue to add the remaining 300 parts of pre-emulsion at a dropping rate of 2.5 parts per minute. After the pre-emulsion is completely added, maintain the temperature for a period of time (1 hour), cool down and discharge the material. Add sodium chloride to the emulsion to break the emulsion. Collect the precipitate, filter, wash, dry, pulverize, and sieve for later use.
[0052] Example 2
[0053] The rest is the same as in Example 1, except that the amount of acrylonitrile is 60 parts, the amount of dimethylaminoethyl methacrylate is 20 parts, and the amount of 1,2-dichloroethylene is 20 parts.
[0054] Example 3
[0055] The rest is the same as in Example 1, except that the amount of acrylonitrile is 60 parts, the amount of dimethylaminoethyl methacrylate is 10 parts, and the amount of 1,2-dichloroethylene is 30 parts.
[0056] Example 4
[0057] The rest is the same as in Example 1, except that the amount of acrylonitrile is 70 parts, the amount of dimethylaminoethyl methacrylate is 20 parts, and the amount of 1,2-dichloroethylene is 10 parts.
[0058] Example 5
[0059] The rest is the same as in Example 1, except that the amount of acrylonitrile is 70 parts, the amount of dimethylaminoethyl methacrylate is 10 parts, and the amount of 1,2-dichloroethylene is 20 parts.
[0060] Example 6
[0061] The rest is the same as in Example 1, except that the monomers used are methacrylonitrile, hydroxypropyl methacrylate and 1,2-dichloroethylene.
[0062] Example 7
[0063] The rest is the same as in Example 1, except that the monomers used are methacrylonitrile, hydroxyethyl methacrylate and 1,2-dichloroethylene.
[0064] Comparative Example 1
[0065] The rest is the same as in Example 1, except that acrylonitrile is not added, that is, 50 parts of dimethylaminoethyl methacrylate and 50 parts of 1,2-dichloroethylene are added.
[0066] Comparative Example 2
[0067] The rest is the same as in Example 1, except that dimethylaminoethyl methacrylate is not added, that is, 80 parts of acrylonitrile and 20 parts of 1,2-dichloroethylene are added.
[0068] Comparative Example 3
[0069] The rest is the same as in Example 1, except that 1,2-dichloroethylene is not added, that is, 20 parts of dimethylaminoethyl methacrylate and 80 parts of acrylonitrile are added.
[0070] Comparative Example 4
[0071] The rest is the same as in Example 1, except that dimethylaminoethyl methacrylate and 1,2-dichloroethylene are not added, that is, only 100 parts of acrylonitrile are added.
[0072] Comparative Example 5
[0073] Commercially available polyvinylidene fluoride (PVDF) was selected and used directly as an adhesive. The model of this commercially available PVDF is PVdF 5130.
[0074] V. Performance Testing and Analysis
[0075] Preparation of the positive electrode sheet:
[0076] The binder powder prepared in the examples and comparative examples was dissolved in N-methylpyrrolidone (NMP). After complete dissolution, it was combined with a conductive agent (Super P), carbon nanotubes (CNTs), and a ternary cathode material (8:1:1 LiNi). 0.8 Co 0.1 Mn 0.1Add O2 together to the mixing tank and stir for 3 hours until the slurry is uniform. Use a scraper to evenly coat the slurry onto the aluminum foil. Dry in a 120℃ oven for 45 minutes, and then press it with a tablet press to obtain the positive electrode sheet.
[0077] (1) Emulsion particle size test
[0078] The emulsions from the examples and comparative examples before demulsification in step 2 were diluted to 0.3 wt%, tested at 25°C, and the particle size of the emulsions was measured using a Malvern Mastersizer 3000 laser particle size analyzer (Malvern). The final result was the average of three tests.
[0079] (2) Peel strength test
[0080] According to GB / T 2792-2014 "Test Method for Peel Strength of Adhesive Tapes", aluminum foil electrode sheets were used as substrates, and a 180° peeling method was adopted. The peeling speed was 10 mm / min, with 5 samples per group, and the average value of the results was taken.
[0081] The peel strength of the adhesive is calculated by the following formula: σ180°=F÷B.
[0082] Where σ180° is the 180° peel strength (N / m), F is the peel force (N), and B is the sample width (m).
[0083] (3) Flexibility test of electrode sheets
[0084] Cut the electrode sheet into 5cm rectangular strips, then wind them onto a 2mm diameter metal cylinder and pull them at a constant speed of 180°. Observe whether the electrode sheet breaks or cracks. The quality of the electrode sheet's flexibility can be represented in the following order: intact without cracks, cracked, slight material loss, material loss, severe material loss, and broken.
[0085] (4) Electrolyte tolerance
[0086] The adhesive was dissolved in NMP solvent to prepare a 4% solids content adhesive solution. The solution was poured into a 5cm×5cm×1cm mold and dried at 70℃. An electrolyte solution with a volume ratio of EP (ethyl propionate):EC (ethylene carbonate):DEC (dimethyl carbonate) = 1:1:1 was prepared. The dried adhesive film was immersed in the electrolyte solution for 48 hours. The ratio of the mass difference before and after immersion to the initial mass was recorded as the electrolyte swelling rate.
[0087] (5) Cyclic performance
[0088] The charge and discharge rates are both 0.5C. After activating the battery with a small current, the average value of the first three discharge capacities is taken as the initial capacity, and the discharge capacities after 50 and 150 cycles are taken as the post-cycle capacity.
[0089] Capacity retention rate = Post-cycle capacity ÷ Initial capacity × 100%.
[0090] (6) High-temperature storage
[0091] The above electrode sheets were made into batteries of the same size. Under full charge and full discharge conditions, the batteries were placed in a 95°C environment for 24 hours, and the ratio of the difference in battery thickness before and after was taken.
[0092] Electrode expansion rate = (Electrode thickness after storage - Initial electrode thickness) ÷ Initial electrode thickness × 100%.
[0093] Table 1
[0094] Example 1 12.4 230.5 Gel-free Complete and without cracks 48.4 Example 2 12.1 234.7 Gel-free Complete and without cracks 75.3 Example 3 11.9 233.8 Gel-free Complete and without cracks 53.5 Example 4 11.6 228.7 Gel-free Complete and without cracks 67.4 Example 5 9.8 229.0 Gel-free Complete and without cracks 41.1 Example 6 11.8 230.2 Gel-free Slight material loss 47.2 Example 7 12.0 234.3 Gel-free Slight material loss 22.4 Comparative Example 1 6.8 233.7 Gel-free Complete and without cracks Dissolve Comparative Example 2 11.2 232.5 Gel-free Complete and without cracks 26.8 Comparative Example 3 12.1 235.7 Gel-free Complete and without cracks 1403.3 Comparative Example 4 4.7 238.7 Gel-free Large pieces of material falling off 20.3 Comparative Example 5 10.8 - gel Slight material loss 51.4
[0095] Table 1 shows that the electrolyte swelling rate is a reliable indicator of electrolyte tolerance. In actual processes, an electrolyte swelling rate of around 40-70% is suitable. If the electrolyte swelling rate is too low, it indicates poor electrolyte wettability of the film, resulting in high ion transport resistance and hindering rapid ion transport. Conversely, if the electrolyte swelling rate is too high, it alters the tensile properties of the film, reducing its mechanical strength. The copolymer described in this invention primarily uses acrylonitrile to provide the adhesive strength. As the acrylonitrile content decreases, the peel force decreases. However, in Comparative Example 4, the polyacrylonitrile's high modulus increases the brittleness and weakens the flexibility of the electrode, leading to severe powder shedding during winding. Furthermore, to increase the density of the electrode material, a certain pressure is typically applied to compress the volume. High modulus generally results in greater hardness, and the adhesive network structure is destroyed after rolling, causing a sharp decrease in adhesive force. The average particle size of the adhesives prepared in Examples 1-7 and Comparative Examples 1-2 is around 232.0 nm, indicating that the method described in this invention has good stability and yields stable product quality. When PVDF is used as a binder, gelation occurs due to the strong alkaline environment, while other binders do not exhibit gelation. When the content of units containing ester functional groups is too high, the electrolyte swelling will increase dramatically or even dissolve, ultimately leading to a sharp decline in battery electrical performance.
[0096] Table 2
[0097]
[0098]
[0099] As shown in Table 2, the capacity retention rates of Examples 1-7 after 150 cycles are higher than those of Comparative Examples 2 and 5. Furthermore, the capacity retention rate reaches approximately 88% after 150 cycles. This excellent performance is attributed to the binder's ability to enhance the contact between the active material, conductive agent, and current collector, as well as its role in stabilizing the electrode structure. The active material and electrolyte form a dense and uniform SEI film, improving cycle performance and extending battery life. Battery swelling is mainly due to the decomposition of carbon impurities on the surface of the active material and the oxidative decomposition of the electrolyte, producing CO2, CO, H2, etc. In Examples 1-7, the C-Cl weakly polar functional group carries conductive materials such as SP. Through the interaction between the cyano strongly polar functional group in (meth)acrylonitrile and the main material, the binder and conductive agent fully encapsulate the active material, inhibiting its decomposition and reducing gas generation. This, in turn, prevents battery swelling and improves battery stability. The binders prepared in Comparative Examples 1, 3, and 4 had poor tolerance to electrolyte or caused severe powder shedding in the prepared electrodes, which no longer met the basic requirements for battery preparation. Therefore, this test was not performed.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.
Claims
1. A copolymer for use as a binder in the positive electrode of lithium-ion batteries, characterized in that, The copolymer's comonomers include lipophilic monomers, amphiphilic monomers, and vinyl chloride derivatives; Based on the total mass of the lipophilic monomer, the amphiphilic monomer, and the vinyl chloride derivative: the mass percentage of the amphiphilic monomer is 10-20%, the mass percentage of the lipophilic monomer is 60-80%, and the mass percentage of the vinyl chloride derivative is 10-30%. The amphiphilic monomer is dimethylaminoethyl methacrylate; The vinyl chloride derivative is 1,2-dichloroethylene; The lipophilic monomers include acrylonitrile and / or methacrylonitrile.
2. A method for preparing a copolymer for use as a binder in the positive electrode of a lithium-ion battery, characterized in that, The preparation of the copolymer of claim 1 specifically includes the following steps: Step 1: Mix the amphiphilic monomer, lipophilic monomer, and vinyl chloride derivative according to the specified ratio to form a reactive monomer, and then prepare a mixture of the reactive monomer and water. Next, add the emulsifier and water to the reactor for deoxygenation, stir until homogeneous, and then slowly add the mixture of the reactive monomer and water while continuously stirring to form a pre-emulsion. The amount of emulsifier used is 3-6% of the total weight of the reactive monomer. Step 2: Divide the pre-emulsion obtained in Step 1 into two parts. Add one part of the pre-emulsion to the reactor for deoxygenation, heat it to 67~72℃, add an initiator to react, and obtain a seed emulsion. Then slowly add the other part of the pre-emulsion. After the reaction is completed, cool it down, demulsify it, filter and dry it to obtain the copolymer. The amount of initiator is 0.05~0.8% of the total weight of the reacting monomers.
3. The method for preparing the copolymer for lithium-ion battery cathode binder according to claim 2, characterized in that, The emulsifier includes anionic emulsifiers and nonionic emulsifiers, wherein the amount of anionic emulsifier is 1 to 2% of the monomer weight, and the amount of nonionic emulsifier is 2 to 4% of the monomer weight.
4. A positive electrode sheet for a lithium-ion battery, characterized in that, The positive electrode sheet includes a positive electrode material, a conductive agent, and a binder; the binder is formulated from the copolymer of claim 1 or the copolymer prepared by the preparation method of claim 2 or 3.
5. The positive electrode sheet for a lithium-ion battery according to claim 4, characterized in that, The amount of binder used accounts for 1 to 3 wt% of the total solid content of the positive electrode slurry.
Citation Information
Patent Citations
Energy storage device
CN111933864A
Anode non-fluorine lithium battery binder and preparation method and application thereof
CN116731241A